11.0k views
1 vote
(cosx/1-sinx)-secx=tanx

1 Answer

5 votes

Answer:

The value of given trigonometrical expression is cos²x + sin²x = 1

Explanation:

Given trigonometrical expression as :

(
(\textrm cos x)/(\textrm 1-sin x) ) - sec x = tan x

Or, (
(\textrm cos x)/(\textrm 1-sin x) ) = tan x + sec x

or, (
(\textrm cos x)/(\textrm 1-sin x) ) = (
(\textrm sin x)/(\textrm cos x) ) + (
(\textrm 1)/(\textrm cos x) )

or, (
(\textrm cos x)/(\textrm 1-sin x) ) = (
(\textrm 1 + sin x)/(\textrm cos x) )

Now, cross multiplying both side

I.e (cos x) × (cos x) = ( 1 - sin x ) × ( 1 + sin x )

or, cos²x = 1 - sin² x

or, cos²x + sin²x = 1

So, Value of expression is cos²x + sin²x = 1

Hence The value of given trigonometrical expression is cos²x + sin²x = 1 answer

User Weiz
by
6.0k points